2003
DOI: 10.1186/1471-2407-3-7
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile of AIDS-related Kaposi's sarcoma

Abstract: Background: Kaposi's Sarcoma (KS) is a proliferation of aberrant vascular structures lined by spindle cells, and is caused by a gammaherpes virus (HHV8/KSHV). Its course is aggravated by coinfection with HIV-1, where the timing of infection with HIV-1 and HHV8 is important for the clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 51 publications
(51 reference statements)
5
25
0
1
Order By: Relevance
“…Recently it was shown by serial analysis of gene expression (SAGE) that HO-1 expression in AIDS-KS biopsy tissue is significantly greater than in control tissue. 60 Here we independently confirm this finding with quantitative RT-PCR results on cutaneous AIDS-KS tissue that show elevated HO-1 mRNA compared with normal skin. Furthermore, immunohistochemistry on oral AIDS-KS lesional tissue revealed increased expression of HO-1 protein compared with normal tissue at the tumor margin.…”
supporting
confidence: 77%
“…Recently it was shown by serial analysis of gene expression (SAGE) that HO-1 expression in AIDS-KS biopsy tissue is significantly greater than in control tissue. 60 Here we independently confirm this finding with quantitative RT-PCR results on cutaneous AIDS-KS tissue that show elevated HO-1 mRNA compared with normal skin. Furthermore, immunohistochemistry on oral AIDS-KS lesional tissue revealed increased expression of HO-1 protein compared with normal tissue at the tumor margin.…”
supporting
confidence: 77%
“…Thus, the resulting infected LECs or BECs are more similar to one another than their uninfected counterparts. This is in agreement with the observation that KS spindle cells do not represent the typical transcriptional profile of LECs nor of BECs, but instead are poorly differentiated, expressing markers of both lymphatic and blood vessel endothelium (Cornelissen et al, 2003;Lagos et al, 2007;Pyakurel et al, 2006b; H.W. .…”
Section: Ks Histogenesis and The Biology Of The Ks Spindle Cellssupporting
confidence: 78%
“…However, other investigators have reported inconsistent CD31 levels in nodular tumor tissue compared to those in blood vessels or compared to CD34 levels (67). The expression of VE-cadherin mRNA in KS tissue was found previously to be increased compared to that in normal skin (18). However, the same study reported increased message levels for MHC-I.…”
Section: Discussionmentioning
confidence: 62%